Capital in the Twenty-first Century. (2nd January 2016) - Morgan-Ayrs, Stuart
Abstract : The book Capital in the Twenty-First Century by Thomas Piketty has been a phenomenon in economics, the social sciences, politics and related disciplines. Piketty examines economic data from several centuries and from several countries, and attempts to draw conclusions about the balance between earned income and capital-driven income, and the resulting outcomes for income distribution and income equality. Piketty illustrates the drastic effects of the Great Depression and two World Wars on capital, and the unexpected positive consequences that have, until recently, led to reductions in income inequality. Piketty then examines the recent slide back towards capital-dominated wealth and its role in increased inequality, and extrapolates how this might lead to future critical inequality and social unrest. Finally, Piketty suggests various possible responses to stave off this crisis, with his preferred option being presented as a progressive system of tax on capital.